The Making of the Greek Genocide : Contested Memories of the Ottoman Greek Catastrophe. - Sjöberg, Erik (War and Genocide Ser., 2016)
During and after World War I, over one million Ottoman Greeks were expelled from Turkey, a watershed moment in Greek history that resulted in hundreds of thousands of deaths. And while few dispute the expulsion's tragic scope, it remains the subject of fierce controversy, as activists have fought for international recognition of an atrocity they consider comparable to the Armenian genocide. This book provides a much-needed analysis of the Greek genocide as cultural trauma. Neither taking the genocide narrative for granted nor dismissing it outright, Erik SjOberg instead recounts how it emerged as a meaningful but contested collective memory with both nationalist and cosmopolitan dimensions.